Brighter spotty lesions on spinal MRI help differentiate AQP4 antibody-positive NMOSD from MOGAD. (May 2022) - Hyun, Jae-Won; Lee, Hye Lim; Park, Jaehong; Kim, Jiah; Min, Ju-Hong; Kim, Byoung Joon; Kim, Seung Woo; Shin, Ha Young; Huh, So-Young; Kim, Woojun; Seo, Ji Won; Kim, Ki Hoon; et al.
In a large acute myelitis cohort, we aimed to determine whether brighter spotty lesions (BSLs)—using the refined terminology—on spinal magnetic resonance imaging (MRI) help distinguish aquaporin-4 antibody-positive neuromyelitis optica spectrum disorder (AQP4-NMOSD) from myelin oligodendrocyte glycoprotein antibody disease (MOGAD). An experienced neuro-radiologist and two neurologists independently analyzed 133 spinal MRI scans (65 from MOGAD and 68 from AQP4-NMOSD) acquired within 1 month of attacks. BSLs were observed in 18 of 61 (30%) participants with AQP4-NMOSD, while none of 49 participants with MOGAD showed BSL ( p < 0.001). BSL during the acute phase would be useful to differentiate AQP4-NMOSD from MOGAD.